Fiber-on-fiber friction measurement using hanging fiber method. Issue 5 (4th May 2018) - Alirezazadeh, Azam; Zarrebini, Mohammad; Ghane, Mohammad; Soltani, Parham
Abstract: Estimation and evaluation of frictional behavior of delicate materials such as textile fibers is contingent upon existence of accurate experimental methods. In this work, the effect of fiber fineness on frictional behavior of polypropylene fibers was investigated using a developed high-precision experimental setup based on hanging fiber method. Fiber fineness was varied by varying the spinning pump speed during production of melt-spun fibers on an industrial scale melt spinning machine. Data acquisition was achieved using Delphi programming software. A geometrical model capable of evaluating the frictional force between two in-contact identical fibers was proposed. Fiber-on-fiber frictional force was expressed by a third degree polynomial function of fiber diameter. The least value of frictional force was found to belong to fiber diameter of 49.1 μm which corresponds to linear density of 15.5 den. It was concluded that frictional behavior of fibers is influenced by factors such as contact point geometry, rate of fiber strain and profile of generated heat.